Pertautan Historisitas dan Relasi Budaya Selayar-Buton - Ahmadin Umar (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2018)
This paper aims to describe the historical and cultural relations between the Selayar people and the Buton people. History records that the Selayar and Buton Islands in the past had important meanings and contributed to the pattern of the historical stage, especially the period of entry and development of Islam in the Sulawesi Peninsula. Various sources say that Selayar people and Buton people have important relationships both genetically, culturally, powerfully and historically. Thus, reading the Selayar History or the History of Buton, both will intersect in their descriptions. In terms of Islamic teachings Selayar and Buton have many similarities, thus reinforcing the notion that both were Islamized by the same Islamic broadcasters. On the other hand, the similarity of dialect and language between the Laiyolo people in Selayar and Walio in Buton is also a sign that the relationship between the two islands in the past is very important. What is the historical setting and the forms of relations between Selayar and Buton, are the core studies of this paper.